Decreased endothelium-dependent vasoconstriction to noradrenaline in acute-stressed rats is potentiated by previous chronic stress: Nitric oxide involvement - Cordellini, S.; Vassilieff, V. S. (Elsevier B.V., 1998)
1. The objective was to determine whether nitric oxide participates in stress adaptive responses. Acute stress (AS) decreased endothelium-dependent vasoconstriction to noradrenaline (NA) in rat aorta [control rat (CR) 3.90+/-0.18, n=22; AS 2.76+/-0.20, n=13; P<0.05].2. Chronic stress exposure previous to AS (CS) potentiated this effect [CS 1.93+/-0.19; n=9; P<0.05 related to CR, P<0.05 related to AS].3. Methylene blue and N-G monomethyl-L-arginine, but not indomethaein, restored the decreased aorta reactivity to NA. 4. No reactivity alteration was observed in aorta without endothelium either in both stress conditions or in the presence of inhibitors. These data show that the nitric oxide participates in stress responses. (C) 1998 Elsevier B.V.
Keywords: acute and chronic stress; endothelium; nitric oxide; reactivity of rat aorta; methylene blue; L-NMMA